IMPROVING READING COMPREHENSION OF THE NINTH-GRADE STUDENTS OF SMP N 2 KUTA IN ACADEMIC YEAR 2022/2023 THROUGH BRAINSTORMING - Ni Nyoman Fenta Sariasih; Ida Ayu Made Sri Widiastuti; Ni Made Wersi Murtini (Academic Journal on English Studies (AJOES), 2023)
Reading is important for us especially for students when they want to explore their knowledge. In fact, most students of IX H at SMP N 2 Kuta in the academic year 2022/2023 faced problems in reading comprehension. The total of the subjects were 32 students. The purpose of this study was to know whether or not reading comprehension could be improved through Brainstorming. Therefore, the researcher conducted classroom action research, which was done in two cycles. The researcher administered research instruments, pre-test, post-test, and questionnaire to collect the data. Based on the research, the results of this study were there was an improvement in the subjects’ reading comprehension. The results showed pre-cycle (56.10), post-test I in cycle I (72.99), and post-test II in cycle II (83.35). at the end of the cycle, the researcher administered a questionnaire to support the data. The results of this study were the reading comprehension of ninth-grade students of SMP N 2 Kuta in the academic year 2022/2023 could be improved through Brainstorming.